Aspectos da dimensão linguístico-discursiva da memória nostálgica: uma análise de editoriais da Revista Ferrovia - Destri, Alana (2018)
The aim of this research is to establish how nostalgic memory, in the subjectivity and objectivity, can be understood through linguistic-discursive point of view. In light of this, nostalgia was the study object for a further deepening on its discursive manifestation and the study of its subjective aspects as signic and ideological phenomenon. The mentioned feeling is remembrance with emotional attachment, something that does not just deal with past: it guides the present and it changes in a distinct way the individual’s view of future. The discursive study establishes itself in the fact that nostalgia, universal and meaningful, cannot be shared nor lived but through signs and, consequently, utterances. To realize this research, a noticeable nostalgic corpus was used: 106 editions of the Revista Ferrovia published between 1935 and 2017. The corpus was mapped, and the nostalgic data produced were organized so, in the light of the theory, they could be analyzed. On theory, several theoretical frameworks were used in a connected way. The linguistic-discursive and socioideological dimensions were represented by Bakthin, Volóchinov and Benveniste; Psychosociology was centered on Sedikides, Vygotsky and Bosi; and in terms of philosophy, Volóchinov and Bauman. As a result, a certain pattern of manifestation and sign operation has been identified and described, broadening the understanding of the phenomenon as something deeply linguistic-discursive and human development promoter.